2021
DOI: 10.3390/jintelligence9020023
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Intelligence and Divergent Thinking—A Meta-Analytic Update

Abstract: This paper provides a meta-analytic update on the relationship between intelligence and divergent thinking (DT), as research on this topic has increased, and methods have diversified since Kim’s meta-analysis in 2005. A three-level meta-analysis was used to analyze 849 correlation coefficients from 112 studies with an overall N = 34,610. The overall effect showed a significant positive correlation of r = .25. This increase of the correlation as compared to Kim’s prior meta-analytic findings could be attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 94 publications
6
52
1
Order By: Relevance
“…Still, however, only seven studies included in this meta-analysis had Gc measures, and thus future studies are needed to provide a more solid test of the role of the intelligence facet for creative achievements, especially across domains. Given that a recent comprehensive meta-analysis (Gerwig et al 2021) of the links between intelligence and divergent thinking did not reveal such a difference for the relationships between divergent thinking and Gc (r = .28), as compared to the relationship between divergent thinking and Gf (r = .23), it seems worthwhile to recommend that future research uses a more comprehensive measurement of intelligence, likely based on the Cattell-Horn-Carroll approach (McGrew 2009) as well as a more fine-grained, domain-specific measurement of creative achievement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, however, only seven studies included in this meta-analysis had Gc measures, and thus future studies are needed to provide a more solid test of the role of the intelligence facet for creative achievements, especially across domains. Given that a recent comprehensive meta-analysis (Gerwig et al 2021) of the links between intelligence and divergent thinking did not reveal such a difference for the relationships between divergent thinking and Gc (r = .28), as compared to the relationship between divergent thinking and Gf (r = .23), it seems worthwhile to recommend that future research uses a more comprehensive measurement of intelligence, likely based on the Cattell-Horn-Carroll approach (McGrew 2009) as well as a more fine-grained, domain-specific measurement of creative achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Initially operationalized as a threshold hypothesis (Karwowski and Gralewski 2013;Weiss et al 2020b) and more recently as a necessary-condition pattern (Karwowski et al 2016), this approach searched for the non-linear relationship between intelligence and creative thinking (Karwowski et al 2016) and achievement (Karwowski et al 2017). However, such complex relationships cannot be reasonably treated in a meta-analysis (see Gerwig et al 2021), and, hence, we focus here mainly on three moderators: domain of creative achievement, intelligence sub-factor, and creative achievement measure.…”
Section: The Intelligence-creative-achievement Relationship and Its Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, however, there has not yet been a major factor analytic study similar to that done by Carroll (1993) which also includes all of the creativity measures as well. The structure of creativity is not agreed upon (e.g., Plucker et al, 2020), however, the incremental validity of the structure of creativity over and above the largely established hierarchical model of aptitudes (Carroll, 1993) is nowhere near understood (for discussion see Plucker and Esping, 2015;Gerwig et al, 2021). Relative to cognitive aptitudes, which are generally measured using standardized tests, there has also been little consensus regarding how creative aptitudes should be assessed (Said-Metwaly et al, 2017).…”
Section: A Thought Experiments To Help Understand the True Overlap Between Measurement Structures: Utilizing The Multi-trait Multi-methodmentioning
confidence: 99%
“…The relationship in these types of studies has been argued to be low by some scholars (e.g., Barron and Harrington, 1981;Kim, 2005). However, a recent meta-analysis by Gerwig et al (2021) on DT tests showed that the overall correlation between creativity and cognitive aptitude was r = 0.25 and that when "employing test-like assessments coupled with becreative instructions and considering DT originality scores" the correlation could be higher (r = 0.31-0.37), concluding that the intelligence-DT correlation is quite robust. Scholars have also argued that true measures of the constructs and their overlap have been underestimated in many studies due to the focus on observable scores (Silvia, 2008).…”
Section: If You Are Creative Are You Also Intellectually Talented?mentioning
confidence: 99%